Post-Operative Outcomes Of Intraocular Lens Implantation With Both Anterior And Posterior Optic Capture In Paediatric Cataract With Insufficient Lens Capsular Support - Kalpit Shah; Smit Shah (Delhi Journal of Ophthalmology)
Objective: To assess the post-operative outcomes of intraocular lens implantation with both anterior and posterior optic capture in terms of visual axis opacification, ocular hypertension, centration of intraocular lens and iris and angle structure irritation in paediatric cataracts with either primary posterior capsular defect or traumatic rupture of anterior capsule or fibrotic anterior capsule or extended anterior capsulorrhexis. Methods: Sixteen (16) eyes of eleven (11) cases of paediatric cataract (5 bilateral and 6 unilateral) of 1 to 4 year of age with either insufficient posterior capsular support or traumatic rupture of anterior capsule or improper anterior capsule to perform anterior continuous curvilinear capsulorrhexis received both anterior and posterior optic capture of posterior chamber intraocular lens (3 piece). Visual axis opacification, intraocular lens centration and intraocular pressure were recorded. The follow up period was 6 to 18 months. Results: Implantation of intraocular lens (3 piece) with both anterior and posterior optic capture was performed successfully in sixteen eyes of paediatric cataract of 1 to 4 year of age. All the eyes had a clear visual axis with no visual axis opacification and maintained clinical centration of intraocular lens with normal intraocular pressure. Conclusion: Anterior and posterior optic capture of intraocular lens is a safe and effective method of treatment of paediatric cataract of 1 to 4 year of age with insufficient lens capsular support in prevention of visual axis opacification.